Ionic Environment Affects Biomolecular Interactions of Amyloid-β: SPR Biosensor Study - Hemmerová, Erika; Špringer, Tomáš; Krištofiková, Zdeňka; Homola, Jiří (International journal of molecular sciences, 2020)
In early stages of Alzheimer's disease (AD), amyloid beta (Aβ) accumulates in the mitochondrial matrix and interacts with mitochondrial proteins, such as cyclophilin D (cypD) and 17β-hydroxysteroid dehydrogenase 10 (17β-HSD10). Multiple processes associated with AD such as increased production or oligomerization of Aβ affect these interactions and disbalance the equilibrium between the biomolecules, which contributes to mitochondrial dysfunction. Here, we investigate the effect of the ionic environment on the interactions of Aβ (Aβ1-40, Aβ1-42) with cypD and 17β-HSD10 using a surface plasmon resonance (SPR) biosensor. We show that changes in concentrations of K+ and Mg2+ significantly affect the interactions and may increase the binding efficiency between the biomolecules by up to 35% and 65% for the interactions with Aβ1-40 and Aβ1-42, respectively, in comparison with the physiological state. We also demonstrate that while the binding of Aβ1-40 to cypD and 17β-HSD10 takes place preferentially around the physiological concentrations of ions, decreased concentrations of K+ and increased concentrations of Mg2+ promote the interaction of both mitochondrial proteins with Aβ1-42. These results suggest that the ionic environment represents an important factor that should be considered in the investigation of biomolecular interactions taking place in the mitochondrial matrix under physiological as well as AD-associated conditions.
Keywords: Surface Plasmon Resonance; povrchová plasmonová rezonance; Amyloid beta-Peptides; Mitochondria; lidé; amyloidní beta-protein; mitochondriální proteiny; Biosensing Techniques; peptidové fragmenty; 17-hydroxysteroidní dehydrogenasy; mitochondrie; peptidylprolylisomerasa F; Peptide Fragments; Alzheimer Disease; biosenzitivní techniky; ionty; Alzheimerova nemoc; 17-Hydroxysteroid Dehydrogenases; Ions; Peptidyl-Prolyl Isomerase F; Mitochondrial Proteins; Humans